Intrinsic Traits Such as Personality and Decision-Making Style are Predictive of Stress in Surrogate Decision-Makers. (July 2023) - Van Scoy, Lauren J.; Bliton, Chloe F.; Smith, Theresa; Badzek, Laurie; Green, Michael J.; Levi, Benjamin H.; Foy, Andrew J.
Introduction: Despite its prominence in psychology, little is known about how personality traits play a role in the stress experiences of surrogate decision-makers. We tested the hypothesis that intrinsic traits (personality and decision-making styles) would be related to surrogates' stress in order to learn whether screening or tailoring interventions based on personality traits could help support surrogate decision-makers.Methods: This pre-specified secondary analysis evaluated data from an interventional study with dyads of patients with advanced chronic illness and their spokespersons. Measures included stress after decision-making or patient death (Impact of Events-Revised), personality (Big Five Index; BFI) and decision-making style (maximization and regret scales). Multivariate linear regressions explored the impact of personality on the stress experience; linear regressions independently modeled the impact of maximization and regret on the stress experience.Results: Of 38 spokespersons, 89.5% were women, 97.4% non-Hispanic, and 29.0% had a college degree or higher. In univariate analyses, total stress was correlated with neuroticism (r = .56, P < .01), higher scores on the regret (r = .55, P < .01) and maximization (r = .48, P < .05). In adjusted models, BFI was significantly associated with total stress (R 2 = 27.08, P = .02). However, only neuroticism was independently associated with total stress.Conclusions: Personality traits, particularly neuroticism, and decision-making styles predicted heightened stress in spokespersons of patients with advanced chronic illness. If ACP interventions are intended to reduce spokesperson stress, personality and decision-making style scales may help identify spokespersons most likely to benefit from ACP interventions.